Effects of heat enhancement for exhaust heat exchanger on the performance of thermoelectric generator. (5th October 2015) - Lu, Chi; Wang, Shixue; Chen, Chen; Li, Yanzhe
Abstract: It is critical that the exhaust heat exchanger of the thermoelectric generator (TEG) that is used in automobile waste heat recovery provides a high heat transfer performance while maintaining a low pressure drop. In this study, incorporating net power output as part of a main comparative parameter, simulations are used to investigate two types of heat transfer enhancements for an exhaust heat exchanger, rectangular offset-strip fins and metal foams. The results for the rectangular offset-strip fins show that there are optimal values of the fin transverse spacing and the fin thickness maximizes the net power output. The use of metal foams can significantly increase the total power output and the efficiency of the TEG, especially foam with low porosity and small pore density (PPI). However, metal foams also produce a high pressure drop and a low net power output. This problem may be solved by using a TEG that combines thermoelectric generation with catalytic conversion. Highlights: Investigated the effects of heat transfer enhancement on the TEG by net power output. For the TEG with offset-strip fin exhaust heat exchanger, optimal fin dimensions exist. The possibility of using metal foams to increase TEG performance was discussed.